ELIMINATING TRAFFIC CONGESTION ON THE ROADS OF TASHKENT CITY AND INCREASING THE ATTRACTIVENESS OF PUBLIC TRANSPORT - Ikramov Akmaljon; Khushvaktov Sardar; Shovkatov Khumoyun; Otaganov Sarvar (Galaxy International Interdisciplinary Research Journal, 2024)
Public transport and reducing the harmful effects of motor vehicles on the environment were critically studied in Tashkent city .